C-reactive protein as a screening test for HIV-associated pulmonary tuberculosis prior to antiretroviral therapy in South Africa. (24th August 2018) - Shapiro, Adrienne E.; Hong, Ting; Govere, Sabina; Thulare, Hilary; Moosa, Mahomed-Yunus; Dorasamy, Afton; Wallis, Carole L.; Celum, Connie L.; Grosset, Jacques; Drain, Paul K.
Abstract : Background: There is an urgent need for more accurate screening tests for tuberculosis (TB). We assessed the diagnostic accuracy of C-reactive protein (CRP) as a screening test for active TB in HIV-infected ambulatory adults. Methods: CRP levels were measured in blood collected at the time of HIV testing. Diagnostic accuracy of CRP for pulmonary TB was calculated (reference standard: TB culture), compared to the WHO 4-symptom screen, consisting of cough, fever, night sweats, and weight loss. Diagnostic accuracy was also calculated for CRP in a larger cohort of HIV-infected adults with a positive symptom screen (reference standard: clinical or microbiological TB). Results: Among 425 HIV-infected outpatients systematically tested for pulmonary TB, TB culture was positive in 42 (10%), 279 (66%) had at least one TB-related symptom and 197 (46%) had a CRP more than 5 mg/l. The sensitivity of CRP and the TB symptom screen to detect TB was the same [90.5%; 95% confidence interval 77.4–97.3] but specificity of CRP was higher than for the TB symptom screen (58.5% vs. 37.1%, P < 0.001). Of persons with no symptoms and normal CRP, 99 (98%) had no TB. In another cohort of 749 patients presenting with at least one TB-related symptom and clinically evaluated, CRP had a sensitivity of 98.7% and specificity of 48.3%. Conclusion: In HIV-infected outpatients, CRP was as sensitive but substantially more specific than TB symptom screening. Use of CRP as a screening tool to exclude active TB could identify the same number of HIV-associated TB cases, but reduce the use of diagnostic sputum testing in TB-endemic regions. Abstract : Supplemental Digital Content is available in the text